1989
DOI: 10.1136/pgmj.65.764.400
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporin treatment of a woman with acquired haemophilia due to factor VIII:C inhibitor

Abstract: Summary A 47 year old woman is reported who had life-threatening bleeding due to the spontaneous development of factor VIII:C inhibitor. Cyclosporin combined with prednisone resulted in a full recovery and complete elimination of antibody even when other therapeutic facilities failed to be effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 9 publications
0
24
1
Order By: Relevance
“…A number of cases have been reported in which cyclosporin A has induced CR after failed first‐line therapy [31,40,47,51,62].…”
Section: Inhibitor Eradicationmentioning
confidence: 99%
“…A number of cases have been reported in which cyclosporin A has induced CR after failed first‐line therapy [31,40,47,51,62].…”
Section: Inhibitor Eradicationmentioning
confidence: 99%
“…Previous studies in a prospective randomized trial have shown that CY is effective as a second-line therapy for many of those who are steroid-resistant [13], and that successful treatment and long-lasting remission was achieved in SLE patients with acquired FVIII inhibitors [8,11]. On the other hand, CsA, alone or with PSL as salvage therapy or as a first-line treatment, has been shown to be effective for acquired hemophilia [23][24][25][26][27][28][29]. It can be administered to patients who do not respond to standard immunosuppressive regimens and is also effective in patients with underlying SLE [3,6,12], such as in our case.…”
Section: Discussionmentioning
confidence: 99%
“…[34][35][36][37][38][39] Cyclosporine (CsA) has also been used for inhibitor suppression. [40][41][42][43] Use of CsA requires monitoring drug levels to ensure efficacy and prevent toxicity. However, its use is limited due to availability of other strategies such as cytotoxic drugs and Rituximab.…”
Section: Discussionmentioning
confidence: 99%